Financial literacy and digital financial literacy / Marini Mamat and Hasyaniza Yahya - Mamat, Marini; Yahya, Hasyaniza (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Basic financial literacy is a skill that is crucial for everybody in making financial decisions from very simple decisions to complex financial decisions. Everyone may use this skill to make decisions on how much money should be used for daily expenses or deciding whether to buy a car or a house. Having these skills enables us to make informed decisions about our financial well-being. For a student, financial literacy is associated with understanding the value of saving money. It is about how they react in spending and saving situations that they might encounter in their daily lives if they do not have enough money to buy something. According to Investopedia, financial literacy is ‘the ability to understand and effectively use various financial skills, including personal financial management, budgeting, and investing’. Whereas Atkinson and Messy (2012), define financial literacy as the combination of awareness, knowledge, skills, attitudes, and behaviours needed to make informed financial decisions and ultimately attain personal financial wellbeing. In other words, it is about how to use money effectively to achieve financial goals.